Global environmental issues : a climatological approach - Kemp, David D., 1943- (Routledge, 1994)
This book provides a balanced account of the global environmental issues which threaten our society and which we neglect at our peril. Analysing both social and environmental components of the issues - global warming, ozone depletion, acid rain and drought - the book offers a valuable integrative approach and a detailed analysis of environmental issues in a clear, non-technical manner. Emphasising the climatological dimension common to all environmental issues, Global Environmental Issues recognises the multi-faceted nature of the issues, their common causes and the p.